Letter - Elger, William
042-0101-001 Scottish Trades Union Congress General Council. William Elger J.P. Secretary. Phone: CENTRAL 3179 33 Elmbank Crescent, Glasgow, October 8th. 1937. Personal. Sir Walter M. Citrine, K.B.E., Transport House, London, S.W.1. Dear Sir Walter, Sir D.M. Stevenson sent me a copy of the letter dated October 1st which he sent to you and he asked if it would be possible for me to have another talk with you. You were not, however, in the office on the morning of the 3rd, but I had a chat with Tewson who will no doubt be reporting to you. I have explained to Stevenson the general difficulty in getting further money for the Scottish Ambulance but he points out that subscriptions direct to him have practically dried up and that under these circumstances the Ambulance ought to return at once. He was hoping that financial assistance could be obtained from the International Fund to permit the Ambulance to remain in Spain at least up to Christmas. I have, of course, held out no hope to him that your Committee will be able to reconsider the matter but I promised that I would write you personally for the purpose of confirming the desperate financial position in which the Ambulance is now placed. Yours truly, Wm Elger 292/946/42/101